Hydrogels as Corneal Stroma Substitutes for In Vitro Evaluation of Drug Ocular Permeation - Susi Burgalassi; Erica Zucchetti; Leonardo Ling; Patrizia Chetoni; Silvia Tampucci; Daniela Monti (MDPI AG, 2022)
Hydrogels are complex hydrophilic structures, consisting of crosslinked homopolymers or copolymers insoluble in water. Due to their controllable bio-physicochemical properties mimicking the morphology of the native extracellular matrix, they are a key part of a lot of research fields, including medicine, pharmaceutics, and tissue engineering. This paper was focused on the preparation and characterization of hydrogels from different blends of polyvinyl alcohol (PVA) with microcrystalline cellulose (MCC) and gelatin (GEL) at various ratios, and from gelatin and chitosan alone to understand their feasibility of utilizing as corneal stroma substitutes in permeability tests for drug candidate molecules in early stages of their development. The characterization was carried out by differential scanning calorimetry, electron microscopy (SEM), water content, mass loss, water permeability, wettability, and tensile stress-strain tests. After the physicochemical characterization, PVA/MCC blend and chitosan proved to be the most promising constructs, showing negligible mass loss after immersion in aqueous medium for two weeks and low hydrodynamic permeability. They were then employed in drug molecules permeation studies and these data were compared to that obtained through excised tissues. The results obtained showed that PVA/MCC hydrogels have similar mechanical and permeability properties to corneal stroma.